Clarifying Standards for Compelled Commercial Speech - Micah L. Berman (Washington University Journal of Law & Policy, 2016)
This article analyzes the compelled commercial speech doctrine within the context of public health warnings and mandated disclosures. Berman details the complex nature of compelled speech, tracing its history and focusing on identifying the appropriate level of constitutional scrutiny that should be applied. Berman then suggests that communities should be given “flexibility to mandate warnings geared towards protecting the public’s health.”
Keywords: First Amendment; Compelled commercial speech doctrine; Public health; Mandated warnings; Zauderer v. Office of Disciplinary Counsel of the Supreme Court of Ohio; R.J. Reynolds Tobacco Co. v. FDA